LEARNING ENGLISH VOCABULARY THROUGH HITS WEST SONGS IN STMIK STIKOM INDONESIA’S STUDENTS (INTEREST AND EFFECTIVENESS) - I Kadek Agus Bisena (Journal of Language, Literature and Teaching, 2020)
Song is a part of a person that can influence the emotions and thoughts. Nowdays millennial generation really like songs both to listen to and sing, especially western songs that are currently become hits songs. Previous studies have examined a lot about the effectiveness of using songs in learning English for young children. In this study, the authors wanted to examine the extent to which STMIK STIKOM Indonesia students' interest in learning English vocabulary through western hits songs, how to implement it properly, and how much effectiveness of using songs in learning English vocabulary. This study was designed using descriptive analysis through a linguistic approach.Keywords: Hits Songs, Western Songs, Learning with Songs.